Bioengenharia de fitomicrobioma na modulação da plasticidade fenotípica de Cucumis sativum - Dorigoni, Vinicius (2021)
Plant growth is directly related to nutrient cycling and the action of microorganisms in the soil, rhizosphere and phyllosphere of plants. The interaction that occurs between a group of microorganisms and plants is characterized as phytomicrobiota, if associated with the host plant can cause changes in the holobionts. These associations can lead to changes in the phytomicrobiome profile resulting in physiological responses in the plant profile, which can be positive or negative, it depends on the intercropped microbial groups and the nutrients available in the soil, and the ones originated in these interactions. This work aimed to evaluate if the application of microbial consortium made in vitro causes changes in the microbiota of cultivated plants of the species Cucumis sativum in a controlled environment. The In loco experiment was carried out in a controlled and protected environment, where the plants were transplanted in pots for their development and controlled application of the microbial consortium. The implementation of the study has taken place in five treatments, namely: control, sterile soil, and the application of the microbial consortium in the phyllosphere, rhizosphere, phyllosphere and rhizosphere combined was carried out.